Manure storage structures for small dairies - Harner, Joseph P.; Murphy, James P. (Kansas Agricultural Experiment Station, 2011)
Kansas environmental regulations require dairy producers with more than 300 animal units (215 mature cows at 1,400 lb, or equivalent weight) to be able to store the manure scraped from freestalls, lots, alleys, and holding pens for 120 days. Many dairies are smaller than the size requiring mandatory registration. However, some are considered a potential environmental problem because of their location near streams or waterways and/or their management and application of manure and may require registration. The intent of the regulations is that manure be stored from December to March to avoid applying it onto frozen ground. Most dairies consider these prime months for manure application, but these are the least desirable from an environmental perspective. Manure applied to frozen ground is not absorbed, and, therefore, the nutrient value of the manure drains from the fields when snow melts or early spring rains are heavy. Three types of storage structures are described.
Keywords: Manure; Storage; Structures; Concrete